2015
DOI: 10.1016/j.ssresearch.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence in neighborhood context: The roles of structural disadvantage, subjective disorder, and emotional distress

Abstract: Most theoretical treatments of intimate partner violence (IPV) focus on individual-level processes. Some researchers have attempted to situate IPV within the larger neighborhood context, but few studies have sought to link structural- and individual-level factors. The current analyses fill a research gap by examining the role of anger and depression in the association between neighborhood disadvantage and IPV. Using data from the Toledo Adolescent Relationships Study (TARS) and the 2000 Census, this study focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 96 publications
7
39
0
Order By: Relevance
“…Overall, this finding supports the application of ecological models to describe the relationship between alcohol use and IPV as well as previous research that has identified an association between community-level social factors (e.g. neighborhood SES, community violence, and norms) and interpersonal violence (O'Campo et al 1995;Raghavan et al 2006;McKinney et al 2009;Raghavan et al 2009;Jain et al 2010;Robinson et al 2011;McKinney et al 2012;Chong et al 2015;Copp et al 2015;Graham et al 2017). To our knowledge, this is the first study to find an association between prevalence of alcohol use among partnered males and IPV, controlling for individual-level partner alcohol use in LMICs.…”
Section: Support For the Indirect And Direct Effect Modelssupporting
confidence: 88%
“…Overall, this finding supports the application of ecological models to describe the relationship between alcohol use and IPV as well as previous research that has identified an association between community-level social factors (e.g. neighborhood SES, community violence, and norms) and interpersonal violence (O'Campo et al 1995;Raghavan et al 2006;McKinney et al 2009;Raghavan et al 2009;Jain et al 2010;Robinson et al 2011;McKinney et al 2012;Chong et al 2015;Copp et al 2015;Graham et al 2017). To our knowledge, this is the first study to find an association between prevalence of alcohol use among partnered males and IPV, controlling for individual-level partner alcohol use in LMICs.…”
Section: Support For the Indirect And Direct Effect Modelssupporting
confidence: 88%
“…A number of academics consider SDT as a mechanism to explain neighbourhood IPV (Benson et al, 2003;Browning, 2002;Copp, Kuhl, Giordano, Longmore, & Manning, 2015;DeKeseredy et al, 2003;Frye, 2007;Frye et al, 2008;Gracia & Herrero, 2007;Gracia et al, 2014;Jackson, 2016;Kiss et al, 2012;Pinchevsky & Wright, 2012;St. Jean, 2007;Uthman, Moradi, & Lawoko, 2009).…”
Section: Social Disorganization Theory and Intimate Partner Violencementioning
confidence: 99%
“…2010; Straus 2011), and the extensive amount of scholarship linking jealousy/cheating and gender attitudes to IPV at the individual level (e.g., Copp et al. 2015; Giordano et al. 2010; Giordano et al.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the few neighborhood‐level investigations of IPV among adolescents and young adults, Jain and colleagues (2010) found that neighborhood social processes (i.e., collective efficacy) partially mediated the effect of neighborhood disadvantage on dating violence. More recently, Copp and colleagues (2015) found that the link between neighborhood disadvantage and IPV was partially explained by individual‐level indicators of emotional distress (anger and depressive symptoms). Thus, based on the more general literature on neighborhood effects as well as the limited work on neighborhoods and IPV, evidence suggests that neighborhood disadvantage “matters,” but that it is insufficient as an explanation for the neighborhood variation in violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation